Answer:
(10, 3)
Step-by-step explanation:
Solve by Substitution
2x − 4y = 8 and 7x − 3y = 61
Solve for x in the first equation.
x = 4 + 2y 7x − 3y = 61
Replace all occurrences of x with 4 + 2y in each e quation.
Replace all occurrences of x in 7x − 3y = 61 with 4 + 2y. 7 (4 + 2y) − 3y = 61
x = 4 + 2y
Simplify 7 (4 + 2y) − 3y.
28 + 11y = 61
x = 4 + 2y
Solve for y in the first equation.
Move all terms not containing y to the right side of the equation.
11y = 33
x = 4 + 2y
Divide each term by 11 and simplify.
y = 3
x = 4 + 2y
Replace all occurrences of y with 3 in each equation.
Replace all occurrences of y in x = 4 + 2y with 3. x = 4 + 2 (3)
y = 3
Simplify 4 + 2 (3).
x = 10
y = 3
The solution to the system is the complete set of ordered pairs that are valid solutions.
(10, 3)
The result can be shown in multiple forms.
Point Form:
(10, 3)
Equation Form:
x = 10, y = 3
Answer:How many fives are in 15? ... How many three-fourths are in 2? ... There are 6 half-sized pieces in 3 wholes. ... and we can see that there are 4 wholes with 6 sixths in each whole, so there are 4\times 6 = 24 sixths in 4. ... Each whole yields a two-thirds and one half of another two-thirds, therefore 3 sets of two-thirds can be ...
Step-by-step explanation:
By applying the law of sines.

Given:
<span>GJ = 10 , ∠J =45° , ∠H = 31°
∴ </span><span>

∴ GH = 10 * sin 45° / sin 31° ≈ 13.7 m
</span>
Answer:
be cautious of the answer
Step-by-step explanation:
Answer:
t-7
Step-by-step explanation: